Validity and Utility of the Patient Health Questionnaire (PHQ)‐2 and PHQ‐9 for Screening and Diagnosis of Depression in Rural Chiapas, Mexico: A Cross‐Sectional Study. Issue 9 (13th February 2017) - Arrieta, Jafet; Aguerrebere, Mercedes; Raviola, Giuseppe; Flores, Hugo; Elliott, Patrick; Espinosa, Azucena; Reyes, Andrea; Ortiz‐Panozo, Eduardo; Rodriguez‐Gutierrez, Elena G.; Mukherjee, Joia; Palazuelos, Daniel; Franke, Molly F.
Abstract : Background: Depressive disorders are frequently under diagnosed in resource‐limited settings because of lack of access to mental health care or the inability of healthcare providers to recognize them. The Patient Health Questionnaire (PHQ)‐2 and the PHQ‐9 have been widely used for screening and diagnosis of depression in primary care settings; however, the validity of their use in rural, Spanish‐speaking populations is unknown. Method: We used a cross‐sectional design to assess the psychometric properties of the PHQ‐9 for depression diagnosis and estimated the sensitivity and specificity of the PHQ‐2 for depression screening. Data were collected from 223 adults in a rural community of Chiapas, Mexico, using the PHQ‐2, the PHQ‐9, and the World Health Organization Quality of Life BREF Scale (WHOQOL‐ BREF). Results: Confirmatory factor analysis suggested that the 1‐factor structure fit reasonably well. The internal consistency of the PHQ‐9 was good (Cronbach's alpha > = 0.8) overall and for subgroups defined by gender, literacy, and age. The PHQ‐9 demonstrated good predictive validity: Participants with a PHQ‐9 diagnosis of depression had lower quality of life scores on the overall WHOQOL‐BREF Scale and each of its domains. Using the PHQ‐9 results as a gold standard, the optimal PHQ‐2 cutoff score for screening of depression was 3 (sensitivity 80.00%, specificity 86.88%, area under receiver operating characteristic curve = 0.89; 95% confidence interval [0.84, 0.94]). Conclusion: The PHQ‐2 and PHQ‐9 demonstrated good psychometric properties, suggesting their potential benefit as tools for depression screening and diagnosis in rural, Spanish‐speaking populations.